(untitled) (Journal of actual problems of jurisprudence, 2018)
The article discussed the theoretical issues of public administration in the field of environmental protection. The purpose of state regulation of quality standards of the environment will help to properly evaluate the impact on the environment. Key words: government regulation, governance, environment, environmental valuation, quality standards of the environment.